PSYCHOLOGICAL SAFETY OF THE STUDENT IN THE EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY: THE SPACE OF FAIRY-TALE THERAPY - Muradyan , Ye.B. (Modern Psychology, 2018)
The article touches upon the issues concerning the psychological safety of the student and the psychological safety of the educational environment of the university. The concept of psychological security of the educational environment of the university is analyzed taking into account its qualitative characteristics and components. The possibility of developing psychological technologies to ensure psychological safety of participants in the educational environment in the university is considered. Attention is drawn to the use of fairy tale -therapeutic training in working with students to achieve their experience of living psychological safety.